Electrophysiological and behavioural responses of the tea geometrid Ectropis obliqua (Lepidoptera: Geometridae) to volatiles from a non‐host plant, rosemary, Rosmarinus officinalis (Lamiaceae). Issue 1 (14th April 2014) - Zhang, Zhengqun; Bian, Lei; Sun, Xiaoling; Luo, Zongxiu; Xin, Zhaojun; Luo, Fengjian; Chen, Zongmao
Abstract BACKGROUND A plant‐based 'push‐pull' strategy for Ectropis obliqua (Prout) (Lepidoptera: Geometridae) is being developed using semiochemicals in the volatiles of Rosmarinus officinalis (Lamiaceae). The aim of this study was to identify and quantify the bioactive components within R. officinalis by gas chromatography–electroantennographic detection (GC‐EAD) and gas chromatography–mass spectrometry (GC‐MS), and to test the antennal and behavioural responses of E. obliqua to these chemicals. The emission dynamics of bioactive chemicals was also monitored. RESULTS GC‐EAD experiments indicated that E. obliqua antennae responded to the following volatile compounds from R. officinalis: myrcene, α‐terpinene, γ‐terpinene, linalool, cis‐verbenol, camphor, α‐terpineol and verbenone, which were the minor constituents. Based on the dose‐dependent antennal and behavioural responses of E. obliqua to these bioactive compounds, myrcene, γ‐terpinene, linalool, cis‐verbenol, camphor and verbenone were found to play a key role in repelling the moths, and the mixture that included all eight compounds was significantly more effective. The maximum emissions of these semiochemicals occurred at nightfall. CONCLUSIONS The specifically bioactive compounds in R. officinalis volatiles are responsible for repelling E. obliqua adults. Results indicate that R. officinalis should be considered as a potential behaviour‐modifying stimulus for 'push' components when developing 'push‐pull' strategies for control of E. obliqua using semiochemicals. © 2014 Society of Chemical Industry